PERAN BADAN USAHA MILIK DESA DALAM PENGEMBANGAN EKONOMI LOKAL MELALUI KEWIRAUSAHAAN SOSIAL - Daulay, Leni Agustina; Alianur, Mudfar; Yustinaningrum, Bettri; Aini, Nurul (Fakultas Keguruan dan Ilmu Pendidikan UNIVA Medan, 2024)
The purpose of this dedication activity is to improve the well-being of the people of Gegarang village with the role of the village owned enterprise agency as a driver and create creative and innovative social entrepreneurship. The approach of this dedication activity is Participatory Action Research (PAR). The results of this dedication show that (1) participants have an understanding of social entrepreneurship and marketing, (2) participants have successfully implemented the process of making onion cakes based on Fish Depik good taste and good product packaging, (3) the success rate of dedication activity seen from the large number of consumers who purchased the product.